La Petite Parade : Festspielausstellung. (Salzburg : Galerie Academia, 1988)
Gonzalez, Julio ; von Jawlensky, Alexej ; Boeckl, Herbert ; Malevich, Kasimir ; Kogan, Nina ; Suetin, Nikolay ; Bissière, Roger ; Lhote, Andre ; Kandinsky, Wassily ; Helion, Jean ; Nebel, Otto ; Dubuffet, Jean ; Kirchner, Ernst Ludwig ; Nicholson, Ben ; Feininger, Lyonel ; Jorn, Asger ; etc.
La Petite Parade : Festspielausstellung, Galerie Academia, Salzburg, 1988
boek